Consejería Nutricional a Pacientes con Trastornos de Coagulación (Hemofilia) Hospital Alfredo Noboa Montenegro, Guaranda. noviembre 2018 - Moreno Freire, Lilia Elizabeth (2019)
The research project called NUTRITIONAL COUNSELING TO PATIENTS WITH DISORDERS OF GOAGULATION (HEMOPHILIA), HOSPITAL "ALFREDO NOBOA MONTENEGRO", GUARANDA. NOVEMBER 2018 was proposed with the objective of providing nutritional counseling to patients with hemophilia at the Alfredo Noboa Montenegro Hospital, by identifying the physical characteristics of the patients and applying anthropometric indicators to be able to know nutritional status, as well as to know the consumption and frequency of Considered foods that should and should not be in the diet of people with coagulation problems, for which it was essential to sustain in a theoretical and conceptual way the object of study and thus define the route to be followed properly, then determine the methodology that is must use according to the type of study, determine the technique and the instrument that was used to collect information that was subsequently processed where a particular data has been established that 3 of the patients have a nutritional status with excesses thus presenting overweight, as well that food intake is less p redominante that of allowed foods for which it is recommended to restructure the diet they maintain and with this improve their nutritional status and avoid diseases that can lead to death. Keywords: counseling, nutrition, hemophilia.